PELESTARIAN DAN PENGOLAHAN TANAMAN OBAT UNTUK MENUNJANG PENGEMBANGAN WELLNESS TOURISM DI DESA WISATA KENDERAN, GIANYAR - Anak Agung Putu Agung Mediastari; Putu Herny Susanti (UNHI Press, 2023)
The global economy has been slowed by the COVID-19 pandemic. Bali's economy has experienced a 12% decline, because of to the reliance of the Balinese people on the tourism sector, one of which is the tourist village of Kenderan in the Gianyar district. Innovative solutions are required to overcome these conditions. Kenderan Village's natural environment has the potential to develop traditional Balinese ingredients made from medicinal plants. However, because the people of Kenderan Village lack the necessary knowledge, it is necessary to assist academics who are experts in their fields. From this background, the following can be formulated: 1) The importance of developing Wellness Tourism products in Kenderan Village; 2) Procedures for developing and processing Wellness Tourism. PKM in Kenderan Village aims to provide knowledge, assistance, development, and processing of medicinal plants into Wellness Tourism products with superior innovation and competitiveness on a local and international scale. Furthermore, this product can be used as an icon for Kenderan Village's Wellness Tourism product. The method used is village potential observation, education on land management procedures, education on the types of plants to be planted, and organic fertilizing and caring for medicinal plants. There will also be workshops on how to turn medicinal plants into Wellness Tourism products.